Features on MDCT that predict surgery in patients with adhesive-related small bowel obstruction. - Wei-Chou Chang; Kai-Hsiung Ko; Chun-Shu Lin; Hsian-He Hsu; Shih-Hung Tsai; Hsiu-Lung Fan; Ho-Jui Tung; Guo-Shu Huang; Ran-Chou Chen (PLoS ONE)
Purpose The purpose of this study was to determine the contribution of multidetector-row computed tomography (MDCT) in the management of adhesion-related small bowel obstruction (SBO) and to identify its predictive value for surgery. Methods We conducted a retrospective review of 151 patients over a 5-year period with the diagnosis of SBO caused by adhesion. These patients were divided into two groups: surgery (n =  63) and observation group (n =  88). Two radiologists blinded to the outcome of the patients evaluated MDCT images retrospectively, recording the bowel diameter, bowel wall thickness, degree of obstruction, air-fluid level, mesenteric fatty stranding, transitional zone, intraperitoneal fluid, close loop, whirl sign, and faeces sign. Statistical analyses were performed using univariate and multivariable analyses. Results Multivariable analysis showed that MDCT demonstrated presence of intraperitoneal fluid (Odds ratio, OR, 4.38), high-grade or complete obstruction (OR, 3.19) and mesenteric fatty stranding (OR, 2.81), and absence of faeces sign (OR, 2.11) were the most significant predictors. When all of the four criteria were used in combination, high sensitivity of 98.4% and specificity of 90.9% were achieved for the prediction for surgery. Conclusion MDCT is useful to evaluate adhesion-related SBO and to predict accurately patients who require surgery. Use of the four MDCT features in combination is highly suggestive of the need for early surgical intervention.